APPLICATION OF SIMPLE INHALATION THERAPY IN PULMONARY TB PATIENTS TO OVERCOME THE INEFECTIVENESS OF BREATH WAY CLEANING - Dini Firdiana Putri; Umdatus Soleha; Firdaus; Rahmadaniar Aditya Putri (Nurse and Holistic Care, 2023)
Background: Inadequate airway clearance is one of the nursing issues that arises during the pulmonary tuberculosis disease process. If untreated, ineffective airway clearance can result in hypoxemia, decreased consciousness, and even cell death.